ANALISIS IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL DALAM MENINGKATKAN MUTU PENDIDIKAN - Rahmawati, Ima; Lestari, Hana; Jamil, Muhamad (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
The way an educational institution ensures that procedures and results meet predetermined criteria is called SPMI. A variety of related literature, including books, journals, and research papers, was collected and examined in this study to pinpoint best practices, barriers, and important variables influencing the efficacy of SPMI. The analysis findings show that the successful implementation of SPMI can improve educational standards through improving teaching, curriculum development, and implementing continuous assessment. SPMI's success cannot be separated from several factors, including the dedication of the management team, employee training, and the involvement of all stakeholders. However, to get the best results, obstacles such as limited resources and reluctance to change must also be overcome. To achieve higher quality education, this research offers useful suggestions for educational institutions to create and implement SPMI.